MANAJEMEN PENGEMBANGAN MUTU LEMBAGA PENDIDIKAN PADA SEKOLAH LUAR BIASA CAHAYA BANGSA KHATULISTIWA PONTIANAK - Nuraini Nuraini (CV. ADIBA AISHA AMIRA, 2022)
Management is a process consisting of actions, planning, organizing, mobilizing and monitoring, which are carried out to determine and achieve the goals that have been set through the use of human resources and other sources. Management of extraordinary education is required to be able to motivate and develop their potential in all aspects of daily life. As in school programs, the potential development of students is an important part of the implementation of the learning process, in order to equip students later in social life. The management of the quality development of the Cahaya Bangsa Khatulistiwa SLB institution in Pontianak plans to develop the quality of the SLB institution, organize the quality of the SLB institution, actualize the quality of the SLB, and supervise the school principal on the supervision of learning development, supervision of teacher and personnel development, supervision of educational forms and services, supervision of the scope special education centers and special service education, and supervision of the development of facilities and infrastructure.